1992
DOI: 10.1152/ajpregu.1992.262.1.r20
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation in human cerebrospinal fluid production measured by magnetic resonance imaging

Abstract: Recent advances in magnetic resonance imaging have made it possible to visualize and quantify flow of cerebrospinal fluid (CSF) in the brain. The net flow of CSF through the cerebral aqueduct was used to measure CSF production in six normal volunteers at different times during a 24-h period. CSF production varied greatly both intra- and interindividually. The average CSF production in each time interval showed a clear tendency to circadian variation, with a minimum production 30% of maximum values (12 +/- 7 ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(156 citation statements)
references
References 0 publications
8
145
2
1
Order By: Relevance
“…In children with hydrocephalus and an intrathecal catheter, circadian rhythms are seen in intracranial pressure, achieving twice the pressure during slow-wave sleep compared to the awake state [149]. In adult volunteers (25-32 years), maximal CSF production was estimated as 42 ± 2 ml/h at 02:00 in the middle of the sleep cycle (range 35-48 ml/h n = 6), whereas the minimum was 12 ± 7 ml/h at 18:00 in the afternoon [129]. This gives a range of around 300-1000 ml CSF produced per day, depending on the time of day that the measurements are made.…”
Section: Pulsatile Flow Of Csfmentioning
confidence: 97%
See 1 more Smart Citation
“…In children with hydrocephalus and an intrathecal catheter, circadian rhythms are seen in intracranial pressure, achieving twice the pressure during slow-wave sleep compared to the awake state [149]. In adult volunteers (25-32 years), maximal CSF production was estimated as 42 ± 2 ml/h at 02:00 in the middle of the sleep cycle (range 35-48 ml/h n = 6), whereas the minimum was 12 ± 7 ml/h at 18:00 in the afternoon [129]. This gives a range of around 300-1000 ml CSF produced per day, depending on the time of day that the measurements are made.…”
Section: Pulsatile Flow Of Csfmentioning
confidence: 97%
“…These techniques are not without methodological issues [22], but the weight of evidence favours a second-to-second pulsatile movement of CSF through the ventricular system, which also changes throughout the day. Early MRI studies by Nilsson et al [129] observed pulsatile CSF flow through the cerebral aqueduct, and CSF velocity varied with cardiac cycle. During cardiac systole, CSF flowed approximately 8 mm/s toward the posterior brain (caudally), then gently back at 5 mm/s to the anterior brain (cranially) during cardiac diastole.…”
Section: Pulsatile Flow Of Csfmentioning
confidence: 99%
“…1a. All subjects underwent the MRI exam during the same time of day (in the afternoon hours) to control for circadian variation, as previously proposed (13). The cine PC sequence was acquired with the AoS in the center of the FOV, such that the wraparound artifact was present in the edges of the FOV, but did not overlap with the desired region of interest (ROI).…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Nilsson et al [31] found that a cranial direction could be considered as a CSF flow displacement toward its main resorption sites at the cranial level.…”
Section: K-mean Methodsmentioning
confidence: 99%
“…The circadian cycle and subject's age also influence the CSF production rate; Nilsson et al [31] found, for healthy volunteers, a variation of 30 ml/h between the minimum and maximum production period at 18:00 pm and 2:00 am respectively. May et al [27] found in elderly healthy individuals a significantly lower CSF production compared with healthy young subjects.…”
Section: Figure 25 Choroid Plexus and Arachnoid Granulations Adaptementioning
confidence: 99%